Endoscopic retrograde brush cytology in patients with primary and secondary malignancies of the pancreas. Issue 4 (April 1979) - Osnes, M; Serck-Hanssen, A; Kristensen, O; Swensen, T; Aune, S; Myren, J
Abstract : Endoscopic retrograde brush cytology (ERBC) was performed in 29 patients with primary pancreatic malignancies verified later by histology. Results were positive in 21 patients, suspicious in five, and negative in three. ERBC performed in seven patients with uncertain findings at endoscopic retrograde cholangiopancreatography (ERCP) was positive for malignancy in six and suspicious in one. Endoscopic aspiration cytology (EAC) performed in 10 patients with primary tumours was positive for malignancy in three, suspicious in two, and negative in five cases. ERBC and/or EAC performed in five cases with secondary tumours were positive for malignancy in one and negative in four. It is concluded that ERBC gives a high rate of positive or suspicious (90%) diagnosis of malignancy in patients with primary pancreatic lesions. In secondary tumours cytology seems to be negative in most cases. The study further shows that many of the malignant tumours found by ERP are secondary lesions. Cytology is often able to detect malignancy when ERP has proved inconclusive.